Genetic diversity, population size, and population stability of common plant species in a Mongolian grassland. (November 2021) - Ishii, Naohiro I.; Takahashi, Masaya; Yoshihara, Yu; Dashzeveg, Nyambayar; Ayush, Tserendejid; Suyama, Yoshihisa; Sasaki, Takehiro
Abstract: Genetic diversity is fundamental for biodiversity, providing an adaptive potential to environmental fluctuations and population stability. This empirical evidence was obtained by comparing the genetic diversity among multiple populations. However, it is controversial whether levels of genetic diversity are related to population stability in inter-specific comparisons, especially among common species in a local community. Additionally, previous studies showed that effective population size predicted from genetic diversity did not necessarily correlate with census population size ( N c), such as the apparent number of individuals. Identifying whether N c can be a surrogate of genetic diversity in a community provides useful information for ecosystem managements. We investigated relationships between genome-wide genetic indices (α and β diversity, and inbreeding coefficient), number of individuals ( N c), and stability over four years in nine common plants at a local scale in Mongolian grasslands. The genetic indices of multiple species were not significantly correlated with N c or its stability. This pattern might be attributed to species-specific identity, such as niche depth at a site, drought tolerance, and differences in stabilization mechanisms via α or β diversity related to N c, and short-term population stability at local scales. Genetic diversity might reflect population size across a regional scale rather than a local scale to ensure stability over long terms and resilience or resistance to environmental extremes. The present study indicated that investigating the genetic diversity-stability relationship for different spatiotemporal scales can lead to understanding the sustainable management of arid grasslands. Highlights: It is debatable whether genetic diversity is related to census population size ( N c) and its stability of multiple species. We investigated relationships between genetic diversity, N c, and its stability in nine plants in the Mongolian grassland. Any genetic indices were not significantly correlated with N c or stability, resulting from species-specific identity.